Hypodontia of mandibular incisors: considerations on the orthodontic treatment - Rédua,Renato Barcellos (2018)
ABSTRACT Hypodontia is the most prevalent craniofacial malformation in mankind. It may present a wide variety of manifestations and, depending on the number and location of missing teeth, it may affect the esthetics, mastication, speech and occlusal balance. This paper discusses the therapeutic approaches to solve this condition, describing a case report with hypodontia of one mandibular lateral incisor, which treatment option included space closure at the region of hypodontia associated with composite resin restorations in the mandibular central incisors. The three-year follow-up after treatment revealed occlusal stability, adequate intercuspation in Class I relationship and excellent micro and macroesthetics.